Dementia Risk and Protective Factors Differ in the Context of Memory Trajectory Groups - Zahodne, Laura B. (J Alzheimers Dis, 2016)
BACKGROUND: Previous research has identified multiple risk and protective factors for late onset Alzheimer’s disease (LOAD). However, it is not known whether these risk and protective factors differ for individuals who are cognitively stable versus those already experiencing declines. OBJECTIVE: This study examined how dementia risk factors differ across subgroups of older adults defined by memory trajectory. This line of research may lead to more individualized risk profiles. METHODS: Risk factors for incident LOAD were compared across previously-validated groups of older adults exhibiting different memory trajectories (“Stable-High,” “Stable-Low,” “Decliner,” “Rapid Decliner”) using stratified Cox regressions. Participants included 2,593 racially/ethnically diverse older adults (mean age of 76 at study entry) in the Washington Heights-Inwood Columbia Aging Project. RESULTS: Predictors of incident dementia differed across trajectory groups: older age only incurred independent risk in stable groups, education did not incur independent risk in the rapidly declining group, depression only incurred independent risk in the stable-low group, stroke incurred independent risk in the two extreme groups, and APOE-ε4 only incurred independent risk in the rapidly declining group. CONCLUSION: The finding that different risk factors for LOAD were associated with specific memory trajectories may reflect the existence of resilience or vulnerability factors that modify the individual influences of risk/protective factors. This study highlights the utility of considering interactions between dementia risk factors and a patient’s unique cognitive history.